2008
DOI: 10.1002/chem.200801568
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Catalytic Activity and Chemoselectivity in Transfer Hydrogenation Catalyzed by Iridium Complex with 4,4′‐Dihydroxy‐2,2′‐bipyridine

Abstract: Transfer hydrogenation catalyzed by an iridium catalyst with 4,4'-dihydroxy-2,2'-bipyridine (DHBP) in an aqueous formate solution exhibits highly pH-dependent catalytic activity and chemoselectivity. The substantial change in the activity is due to the electronic effect based on the acid-base equilibrium of the phenolic hydroxyl group of DHBP. Under basic conditions, high turnover frequency values of the DHBP complex, which can be more than 1000 times the value of the unsubstituted analogue, are obtained (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 56 publications
(85 reference statements)
3
90
1
Order By: Relevance
“…This trend is in agreement with those made with HCOONa as the reducing agent in water. 13 The used CdS sample was filtered and further characterized. No iridium nanoparticles could be observed in the TEM image (Fig.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is in agreement with those made with HCOONa as the reducing agent in water. 13 The used CdS sample was filtered and further characterized. No iridium nanoparticles could be observed in the TEM image (Fig.…”
Section: +mentioning
confidence: 99%
“…13 This inspires us to improve the efficiency in the current photocatalytic system by the optimization of the pH value of solution. As shown in Fig.…”
Section: +mentioning
confidence: 99%
“…For example, Periana and coworkers investigated the heterolytic C À H bond activation of methane and benzene with a cyclometalated Pt II complex as well as catalytic methane hydroxylation using an Ir III NNC pincer complex in acidic solution; [7,8] another study deals with transfer hydrogenation mediated by a cyclometalated Ir III compound. [9] 2,2'-Bipyridine (bipy) and related heterocycles, which are versatile ligands in the coordination chemistry of transition metals, [10] are well suited for the formation of cyclometalated compounds. Moreover, it has been shown that cyclometalated [PtA C H T U N G T R E N N U N G (bipyÀH)] + (1) can formally dehydrosulfurize a variety of thioethers in the gas phase; [11] especially in the reaction with dimethyl sulfide, efficient oxidative C À C bond coupling and concomitant formation of neutral ethene was observed.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the scientific community has been directing considerable research effort into catalytic transfer hydrogenation, [6][7][8] which favors use of hydrogen donors (alcohols, diimides, amines, hydrocarbons or formic acid) and avoids molecular hydrogen. Ruthenium, 9-11 rhodium, [12][13][14][15] iridium, [16][17][18][19] and nickel 20 are the metals most frequently used as catalysts. Organocatalytic transfer hydrogenation using dihydropyridines as hydride donors and Brönsted acid catalysis has also been intensively investigated.…”
Section: Introductionmentioning
confidence: 99%